Developmentally Driven Changes in Adipogenesis in Different Fat Depots Are Related to Obesity - Breitfeld, Jana; Kehr, Stephanie; Müller, Luise; Stadler, Peter F.; Böttcher, Yvonne; Blüher, Matthias; Stumvoll, Michael; Kovacs, Peter (Frontiers in Endocrinology, 2020)
Subcutaneous (sc) and visceral (vis) adipose tissue (AT) contribute to the variability in pathophysiological consequences of obesity and adverse fat distribution. To gain insights into the molecular mechanisms distinguishing vis and sc fat, we compared the transcriptome during differentiation of immortalized adipocytes from murine epididymal (epi) and inguinal (ing) AT. RNA was extracted on different days of adipogenesis (-2, 0, 2, 4, 6, 8) and analyzed using Clariom™ D mouse assays (Affymetrix) covering >214,900 transcripts in >66,100 genes. Transcript Time Course Analysis revealed 137 differentially expressed genes. The top genes with most divergent expression dynamics included developmental genes like Alx1, Lhx8, Irx1/2, Hoxc10, Hoxa5/10 and Tbx5/15. According to pathway analysis the majority of the genes were enriched in pathways related to AT development. Finally, in paired samples of human vis and sc AT (N=63), several of these genes exhibited depot-specific variability in expression which correlated closely with body mass index and/or waist-to-hip ratio. In conclusion, intrinsically programmed differences in gene expression patterns during adipogenesis suggest that fat depot specific regulation of adipogenesis contributes to individual risk of obesity.